Pengembangan Modul Pemrograman Berorientasi Objek Berbasis Problem-Based Learning Prodi Pendidikan Teknologi Informasi - Hasanah, Fitria Nur; Astuti, Cindy Cahyaning; Taurusta, Cindy (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
The purpose of this development research was to produce a problem-based learning object-oriented programming module in Information Technology Education Study Program and to know the feasibility level of the module. Development of modules using the 4D development model was adopted from Thiagarajan. The modules were validated by material experts and instructional media experts and were tested in limited groups. This research produced a product based on problem-based learning print module. The module was equipped with relevant illustration images and job sheets that directed the students to solve problems. The module feasibility level by material experts was 91.6 percent in very feasible criteria and 97 percent in very feasible criteria by the media experts. The results of limited group trials reached the level feasibility of 86.8 percent with very decent criteria. Based on the feasibility test, it can be concluded that the problem-based learning module could be used for the learning process.